Detection of Helicobacter pylori using nested polymerase chain reaction and rapid urease test in gastric biopsy samples - Hamiyet DÖNMEZ ALTUNTAŞ,; Kadri GÜVEN, (Turkish Journal of Gastroenterology, 2019)
-